miR-139-5p activates ferroptosis by inhibiting the expression of HMG-CoA reductase to inhibit the progression of glioma - Zhongsheng You; Fei Wu; Yaofeng Zheng; Hongling Yang; Jianbo Ye; Hongyi Cai; Chuangcai Luo; Yang Liu; Yiquan Ke; Xiangdong Xu (Cell Death Discovery)
Abstract Glioma is the most aggressive and common tumour in the central nervous system. It has been reported that miR-139-5p plays an important role in regulating tumour progression. However, whether miR-139-5p affects the progression of glioma and the specific mechanism remains to be explored. Through experiments involving down-regulation or overexpression of miR-139-5p and treatment with simvastatin (SIM), qRT-PCR and Western Blot were used to detect the expression levels of related genes. Transmission electron microscopy (TEM) and corresponding kits were used to detect the changes in ferroptosis and cholesterol content in glioma cells. RNA-seq analysis was used to explore the specific mechanism by which miR-139-5p regulates ferroptosis. Our results demonstrate that miR-139-5p expression is significantly reduced in glioma cells compared to normal glial cells and is associated with poor prognosis. Overexpression of miR-139-5p promotes ferroptosis and inhibits tumour cell proliferation by downregulating HMG-CoA reductase (HMGCR) expression, consequently hindering glioma progression. Additionally, we found a synergistic effect between miR-139-5p overexpression and SIM treatment in promoting ferroptosis in gliomas. These findings suggest that miR-139-5p could serve as a potential therapeutic target for glioma treatment, particularly in combination with SIM. This study demonstrated that miR-139-5p promoted ferroptosis in glioma cells by down-regulating HMGCR expression and cholesterol synthesis. Moreover, miR-139-5p and SIM had a synergistic effect in promoting ferroptosis to prevent glioma progression.